Scale dependence and scale invariance in hydrology - Sposito, Garrison 1939- (Cambridge University Press, 1998)
Whether processes in the natural world are dependent or independent of the scale at which they operate is one of the major issues in hydrologic science. In this volume, leading hydrologists present their views on the role of scale effects in hydrologic phenomena occurring in a range of field settings, from the land surface to deep fractured rock. Self-contained and thought-provoking chapters cover both theoretical and applied hydrology. They provide critical insights into important topics such as general circulation models, floods, river networks, vadose-zone processes, groundwater transport, and fluid flow through fractured media. This book is intended as an accessible introduction for graduate students and researchers to some of the most significant questions and challenges that will face hydrologic science in the twenty-first century